Stigmatization in Patients With Psoriasis: A Mini Review - Zhang, Hanlin; Yang, Zihan; Tang, Keyun; Sun, Qiuning; Jin, Hongzhong (Frontiers in Immunology, 2021)
Psoriasis is a chronic and recurrent immune-related skin disease that often causes disfigurement and disability. Due to the visibility of lesions in patients and inadequate understanding of dermatology knowledge in the general public, patients with psoriasis often suffer from stigma in their daily lives, which has adverse effects on their mental health, quality of life, and therapeutic responses. This review summarized the frequently used questionnaires and scales to evaluate stigmatization in patients with psoriasis, and recent advances on this topic. Feelings of Stigmatization Questionnaire, Questionnaire on Experience with Skin Complaints, and 6-item Stigmatization Scale have been commonly used. The relationship between sociodemographic characteristics, disease-related variables, psychiatric disorders, quality of life, and stigmatization in patients with psoriasis has been thoroughly investigated with these questionnaires. Managing the stigmatization in patients with psoriasis needs cooperation among policymakers, dermatologists, psychologists, psychiatrists, researchers, and patients. Further studies can concentrate more on these existing topics, as well as other topics, including predictors of perceived stigmatization, stigmatization from non-patient groups, influence of biologics on stigmatization, and methods of coping with stigmatization.